2017
DOI: 10.1016/j.pmrj.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

A Guide to Inpatient Cancer Rehabilitation: Focusing on Patient Selection and Evidence‐Based Outcomes

Abstract: Cancer inpatients commonly suffer from impairments that can prohibit safe discharge home from the acute care inpatient medical service and thus require transfer to a post-acute inpatient rehabilitation facility. It has been demonstrated in multiple studies that cancer rehabilitation inpatients are able to make statistically significant functional improvements and at a similar pace as their non-cancer counterparts. Medical fragility and reimbursement regulations are concerns that affect acceptance and triage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Brain tumor patients whether due to a primary brain tumor or metastatic brain tumor are general felt to fall under the brain injury diagnosis. [14, 15] Interestingly, MD Anderson Cancer Center is exempt from the Prospective Payment System and does not have to adhere to the 60% rule. Despite this, neurologic tumors were still the largest group of primary tumors admitted to the IRF there (although the proportion was less compared to Shirley Ryan Ability Lab or the national data from Mix et al).…”
Section: Introductionmentioning
confidence: 99%
“…Brain tumor patients whether due to a primary brain tumor or metastatic brain tumor are general felt to fall under the brain injury diagnosis. [14, 15] Interestingly, MD Anderson Cancer Center is exempt from the Prospective Payment System and does not have to adhere to the 60% rule. Despite this, neurologic tumors were still the largest group of primary tumors admitted to the IRF there (although the proportion was less compared to Shirley Ryan Ability Lab or the national data from Mix et al).…”
Section: Introductionmentioning
confidence: 99%
“…This lower admission rate may be due to a number of factors including under-referral as well as insurance denial of services 11 . A concern that is often cited in the cancer population is the ability to participate in therapy requirements at post-acute care facilities, which can range from 1-3 hours total per day of physical therapy, occupational therapy or speech therapy 17 . Despite this postulated apprehension, previous studies have found that cancer patients make signi cant functional gains during IRF stay, comparable to gains made for stroke, traumatic brain injury and spinal cord injury patients for which IRF is commonly recommended [18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the guarantee of frequent and close controls, and follow-up exams of these patients in their centre during the first 100 days, is in fact more important than physical and psychological rehabilitation during this time period. The main reason for this difficult situation is simply the lack of rehabilitation facilities experienced in alloHCT treatment that are close to transplant centres [ 51 ].…”
Section: Acute Rehabilitation As An Inpatient Later In the Time Coursementioning
confidence: 99%